A Ligand‐free Copper‐promoted Dimerization of Perylene Bisimide by Aromatic CC Homocoupling and CH Activation. Issue 7 (21st June 2013) - Lu, Xiuqiang; Dong, Huanli; He, Ping; Zhang, Xiaotao; Liu, Jie; Meng, Qing; Jiang, Lang; Wang, Zhaohui; Zhen, Yonggang; Hu, Wenping
<x xml:space="preserve">Abstract</x> Dimer‐mite: A ligandless, copper‐mediated dimerization of tetrachlorinated perylene bisimide towards fully conjugated, triply linked tetrachlorinated di(perylene bisimides) through CC homocoupling and CH activation has been developed. This method provides an efficient and economical protocol for the construction of condensed ring systems of perylene bisimides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>